2012
DOI: 10.1029/2012gl053196
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability of global ocean mixing inferred from Argo profiles

Abstract: [1] The influence of turbulent ocean mixing transcends its inherently small scales to affect large scale ocean processes including water-mass transformation, stratification maintenance, and the overturning circulation. However, the distribution of ocean mixing is not well described by sparse ship-based observations since this mixing is both spatially patchy and temporally intermittent. We use strain information from Argo float profiles in the upper 2,000 m of the ocean to generate over 400,000 estimates of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
237
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(287 citation statements)
references
References 34 publications
33
237
0
Order By: Relevance
“…This geography qualitatively agrees with the fine structure observed by Argo (Fig. 1 in Whalen et al, 2012) and theoretical predictions of intensified parametric subharmonic instability (e.g., MacKinnon and Winters, 2005). However, interleaving of weak and strong mixing layers is a common feature of the K d inverse estimate.…”
Section: Estimated Turbulent Transport Parameterssupporting
confidence: 77%
See 2 more Smart Citations
“…This geography qualitatively agrees with the fine structure observed by Argo (Fig. 1 in Whalen et al, 2012) and theoretical predictions of intensified parametric subharmonic instability (e.g., MacKinnon and Winters, 2005). However, interleaving of weak and strong mixing layers is a common feature of the K d inverse estimate.…”
Section: Estimated Turbulent Transport Parameterssupporting
confidence: 77%
“…2, 9; regions in green) likely denote large uncertainties reflecting that available data constraints are insufficiently sensitive to prompt sizable parameter adjustments (as noted by Liu et al, 2012). The relatively weak values of K d − K d in the ACC (as compared with, e.g., Whalen et al, 2012, but not with Liu et al, 2012) may be one example. Similarly, the fact that K d − K d is generally muted in the abyss (albeit with notable exceptions in the Southern Ocean) is not surprising and does not imply that K d is a precise first guess.…”
Section: Assessment Of Uncertaintiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Whalen et al [2012] have found the insensitivity to the choice of the segment length from 200 to 240 m in the calculation of the turbulent mixing. The surface 300 m layer was removed to avoid the overestimation in the presence of sharp pycnoclines , and also the analysis of the surface mixed layer where the assumption that turbulent mixing is primarily a result of wave breaking resulting from the downscale cascade is not valid.…”
Section: Fine-scale Parameterization Methodsmentioning
confidence: 99%
“…For vertical turbulent and molecular mixing, measurements of T, S, and velocities at vertical spatial scales of centimeters are required throughout the entire water column and at horizontal spacing spanning the entire ocean, a suite of measurements not easy to collect (Killworth, 1998). In the absence of direct observations, mixing fields are often inferred from indirect observations and theories (e.g., Kunze et al, 2006;Whalen et al, 2012;Cole et al, 2015). At high latitudes, lack of knowledge in the three-dimensional distribution of these mixing fields is one of the primary reasons the Arctic Ocean's mean horizontal and vertical hydrographic structure is not well reproduced in numerical models (Holloway et al, 2007;Nguyen et al, 2011;Ilicak et al, 2016).…”
Section: Itp Data As Constraints For Estimating Ocean Model Parametersmentioning
confidence: 99%